Pengaruh Fasilitas Belajar Dan Minat Belajar Terhadap Prestasi Belajar Siswa Kelas Vii Smp Negeri 6 Pematang Siantar Tahun Ajaran 2022/2023 - Yen Jelita Tampubolon; Anggun Tiur Ida Sinaga; Paulina Herlina N Sirait (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to obtain knowledge regarding the influence of learning facilities and interest in learning on the learning achievement of class VIII students at SMP N6 Pematang Siantar Academic Year 2022/2023. This type of research is qualitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 25. The population in this study was 171 people, and the sample used was 120 people. The sampling technique used was proportionate stratified random sampling. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of the research state that: 1) there is a positive influence of learning facilities on student learning achievement. This result can be seen in the t test where the t value of learning facilities (2.016) > t table value (1.6580). 2) there is a positive and significant influence of interest in learning on learning achievement. This result can be seen in the t test where the t value of interest in learning (8.802) > t table value (1.6580) which means that this variable is significant. 3) Learning facilities and interest in learning together influence learning achievement. This result can be seen in the F test where the Fcount value (77.462) > Ftable value (2.682). The R Square coefficient of determination test is known to be 0.570, which means that 57% of the variables of learning facilities and interest in learning influence the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar for the 2022/2023 academic year and 43% is the influence of other variables not examined in this research. .